Antibacterial, antioxidant and anti-inflammatory activities of red, brown, and black sorghum (Sorghum bicolor) cultivated in a dry land area - LINCE MUKKUN; ENOS TANGKE ARUNG Tangkearung; MAYA ISMAYATI; YASINTA LETEK KLEDEN; PRISCA DEVIANI PAKAN; ELIAS ST. O. NGURU; NETTY MARIA NAIBAHO (Society for Indonesian Biodiversity, 2024)
Abstract. Mukkun L, Arung ET, Ismayati M, Kleden YL, Pakan PD, Nguru ESO, Naibaho NM. 2024. Antibacterial, antioxidant and anti-inflammatory activities of red, brown, and black sorghum (Sorghum bicolor) cultivated in a dry land area. Biodiversitas 25: 2560-2569. In an effort to find natural sources for skin treatment, several varieties of sorghum (Sorghum bicolor L. Moench) were evaluated. Sorghum is one of the most important food crops, it is mainly grown in semi-arid areas, because of its ability to tolerate both drought and low soil fertility. This study aimed to evaluate the antibacterial, antioxidant, and anti-inflammation properties of seven types of colored sorghums. Two species of bacteria, Propionibacterium acnes and Staphylococcus epidermis, were used to evaluate the antibacterial properties of sorghum extracts. The results exhibited that sorghum has potent antibacterial activity against P. acnes, ranging from very strong to strong, while moderate to high against S. epidermis. The red Sumba exhibited very strong antibacterial properties against P. acnes and S. epidermis. The brown Sumba showed the highest level of antioxidant activity among other types of sorghum, measured at 82.21%. The brown Sabu had high anti-inflammation activity with an IC50 value of 70.92 ?g/mL. The phenolic compounds found in colored was 57.69 to 64.12% Gallic Acid Equivalent (GAE), dry weight. Six major bioactive compounds were detected using GC-MS, including methyl ester of hexadecanoic acid, n-hexadecanoic acid, methyl ester of 11,14-octadecadienoic acid, 9,12-octadecadienoic acid (Z, Z)-, methyl ester of 4-octadecenoic acid, cis-13,16-docasadienoic acid, aspidospermidin-17-ol, and 1-acetyl-19,21-epoxy-15,16-dimethoxy. Further studies are needed to investigate the effect of compounds extracted from colored sorghums as a commercial anti-acne in the future.